AAPM task group report 303 endorsed by the ABS: MRI implementation in HDR brachytherapy—Considerations from simulation to treatment. Issue 8 (20th June 2022) - Prisciandaro, Joann; Zoberi, Jacqueline (Esthappan); Cohen, Gil'ad; Kim, Yusung; Johnson, Perry; Paulson, Eric; Song, William; Hwang, Ken‐Pin; Erickson, Beth; Beriwal, Sushil; Kirisits, Christian; Mourtada, Firas
Abstract: The task group (TG) on magnetic resonance imaging (MRI) implementation in high‐dose‐rate (HDR) brachytherapy (BT)—Considerations from simulation to treatment, TG 303, was constituted by the American Association of Physicists in Medicine's (AAPM's) Science Council under the direction of the Therapy Physics Committee, the Brachytherapy Subcommittee, and the Working Group on Brachytherapy Clinical Applications. The TG was charged with developing recommendations for commissioning, clinical implementation, and on‐going quality assurance (QA). Additionally, the TG was charged with describing HDR BT workflows and evaluating practical consideration that arise when implementing MR imaging. For brevity, the report is focused on the treatment of gynecologic and prostate cancer. The TG report provides an introduction and rationale for MRI implementation in BT, a review of previous publications on topics including available applicators, clinical trials, previously published BT‐related TG reports, and new image‐guided recommendations beyond CT‐based practices. The report describes MRI protocols and methodologies, including recommendations for the clinical implementation and logical considerations for MR imaging for HDR BT. Given the evolution from prescriptive to risk‐based QA, an example of a risk‐based analysis using MRI‐based, prostate HDR BT is presented. In summary, the TG report is intended to provide clear and comprehensive guidelines and recommendations for commissioning, clinical implementation, and QA for MRI‐based HDR BT that may be utilized by the medical physics community to streamline this process. This report is endorsed by the American Brachytherapy Society.